2011
DOI: 10.1007/s00234-011-0907-6
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted imaging in acute demyelinating myelopathy

Abstract: Acute demyelinating spinal cord lesions show a uniform restricted diffusion pattern. Clinicians and neuro-radiologists should be aware that this pattern is not necessarily confirmatory for an ischaemic aetiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
(37 reference statements)
0
10
0
Order By: Relevance
“…We and others have reported that acute demyelinating lesions in patients with RRMS may have restricted diffusion and may be non-enhancing on brain MRI similar to patients with acute stroke [21,22]. Comparison of age-matched ischemic stroke and RRMS patients provided no significant differences in both volume and count of PVL adjacent to any of the four anatomic regions and in total PVL volume and count (Table 4).…”
Section: Discussionmentioning
confidence: 85%
“…We and others have reported that acute demyelinating lesions in patients with RRMS may have restricted diffusion and may be non-enhancing on brain MRI similar to patients with acute stroke [21,22]. Comparison of age-matched ischemic stroke and RRMS patients provided no significant differences in both volume and count of PVL adjacent to any of the four anatomic regions and in total PVL volume and count (Table 4).…”
Section: Discussionmentioning
confidence: 85%
“…28 Recently, a restricted diffusion pattern has been found in acute demyelinating spinal cord lesions. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical use of diffusion‐weighted imaging (DWI) for evaluation of spinal pathology is increasing. The greatest benefits of DWI in the spine are in the settings of spinal cord infarctions, contusions and demyelinating lesions, and in the identification of spinal metastases and inclusion cysts such as dermoids or epidermoids . In adults, DWI has been shown to be helpful in differentiating malignant from nonmalignant vertebral compression fractures …”
Section: Introductionmentioning
confidence: 99%
“…The greatest benefits of DWI in the spine are in the settings of spinal cord infarctions, contusions and demyelinating lesions, and in the identification of spinal metastases and inclusion cysts such as dermoids or epidermoids. [2][3][4] In adults, DWI has been shown to be helpful in differentiating malignant from nonmalignant vertebral compression fractures. 5 The reduced field of view (rFOV) DWI technique used in this study replaces the slice selective 90 degree excitation pulse with a 2-dimensional 90 degree spatially selective pulse that reduces the FOV in the phase encoding direction.…”
Section: Introductionmentioning
confidence: 99%